1997
DOI: 10.1074/jbc.272.45.28672
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Sites Required for Down-regulation of Na+/H+ Exchanger NHE3 Activity by cAMP-dependent Protein Kinase

Abstract: We recently identified a region within the cytoplasmic C-terminal tail of the Na

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
153
2
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
4
2

Relationship

2
8

Authors

Journals

citations
Cited by 144 publications
(163 citation statements)
references
References 38 publications
(53 reference statements)
5
153
2
3
Order By: Relevance
“…The cAMP-dependent acute inhibition can be due to a change in pH i sensitivity or V max of the transporter (35) or even due to an acute decrease in surface expression (6). Although the mechanisms by which cAMP signals acutely inhibit NHE3 are diverse, protein phosphorylation by PKA type II has been demonstrated to be an essential common event (6,8,37). Based on the data from this study, it can be speculated that Shank2 binding can blunt the effect of cAMP-PKA either by changing the phosphorylation status of NHE3 independent of the EBP50⅐ezrin⅐PKA complex or by competing with the PDZ-based scaffolds associated with PKA-anchoring protein, thus breaching the formation of protein complexes that would lead to PKA-dependent phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…The cAMP-dependent acute inhibition can be due to a change in pH i sensitivity or V max of the transporter (35) or even due to an acute decrease in surface expression (6). Although the mechanisms by which cAMP signals acutely inhibit NHE3 are diverse, protein phosphorylation by PKA type II has been demonstrated to be an essential common event (6,8,37). Based on the data from this study, it can be speculated that Shank2 binding can blunt the effect of cAMP-PKA either by changing the phosphorylation status of NHE3 independent of the EBP50⅐ezrin⅐PKA complex or by competing with the PDZ-based scaffolds associated with PKA-anchoring protein, thus breaching the formation of protein complexes that would lead to PKA-dependent phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is possible that the association of NHE3 with megalin causes inactivation of transport activity. However, it is known that phosphorylation of NHE3 by protein kinase A causes inhibition of NHE3 activity (36,37). It is possible that phosphorylation of NHE3 causes both its inactivation and its association with megalin.…”
Section: Fig 10 Namentioning
confidence: 99%
“…We recently have shown that A 1 R-mediated inactivation of NHE3 is dependent on protein kinase C (PKC) (7,9). Phosphorylation of NHE3 is an early event in regulation of NHE3 by protein kinases (36,37,55,56). Elimination of phosphoserines on NHE3 may disrupt CPA regulation of NHE3 activity.…”
Section: Identification Of Structural Elements Required For Downregulmentioning
confidence: 99%